The identification and appraisal of assessment tools used to evaluate metatarsus adductus: a systematic review of their measurement properties - Nicole Marshall; Emily Ward; Cylie M. Williams (Journal of Foot and Ankle Research, 2018)
Abstract Background Metatarsus adductus is the most common congenital foot deformity in newborns. It involves adduction of the metatarsals at the Lisfranc joint. A systematic literature review was conducted to investigate the following question: What tools are used to identify and quantify metatarsus adductus and how reliable, valid and responsive are they? Methods The following electronic databases were searched for studies describing tools for the identification and quantification of metatarsus adductus in adults and children published from inception to June 2016: Ovid MEDLINE, Embase, CINAHL, Scopus, Web of Science and AMED. Two researchers initially searched all articles by screening titles and abstracts. If there was any doubt as to an article’s eligibility, the full text paper was retrieved. Reference lists and citations of all retained studies were examined in an attempt to locate further studies. Articles were excluded if they were not in English or described other congenital foot conditions that did not include metatarsus adductus. Studies included in the review reporting measurement properties of measurement tools were critically appraised using the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) critical appraisal tool. Results There were 282 articles screened by title and abstract and 28 articles screened from full text. Fifteen articles were included and nine had data that were extractable for appraisal using the COSMIN critical appraisal tool. Techniques to measure metatarsus adductus included the heel bisector method, photocopies, ultrasound, footprints, dynamic foot pressure and radiographs. There was a paucity of quality data reporting the reliability, validity or responsiveness for measuring metatarsus adductus. Several radiographic angles showed good reliability (intraclass correlation (ICC) – 0.84, 0.97) in adults during pre-operative planning. Conclusion There have been multiple assessment techniques proposed for quantification of metatarsus adductus, but there is paucity of reliability, validity or responsiveness to measurement data about these techniques, especially in relation to the paediatric population. Further consideration of measurement testing is required to determine if the most common non-radiographic measures of metatarsus adductus are acceptable for clinical use.